Neanderthals and modern humans : an ecological and evolutionary perspective - Finlayson, Clive, 1955- (Cambridge studies in biological and evolutionary anthropology, 2004)
Why did the Neanderthals go extinct? Were they just out-competed by our own ancestors? This book provides compelling evidence that populations of both species existed side by side for some time, and that it was the Neanderthals' failure to adapt fast enough to changing climatic conditions that sounded their death-knell.